(untitled) (Eurasian Scientific Herald, 2025)
Assessing the main pathophysiological changes in individuals with chronic renal failure—which is characterized by either a persistent, substantial drop in glomerular filtration rate or a prolonged, irreversible loss of kidney tissue—is the aim of the study. It is also distinguished by a variety of clinical signs and indications as well as a broad spectrum of metabolic abnormalities.